Alterations in B cell development, CDR-H3 repertoire and dsDNA-binding antibody production among C57BL/6 ΔD−iD mice congenic for the lupus susceptibility loci sle1, sle2 or sle3. (2nd January 2017) - Khass, Mohamed; Schelonka, Robert L.; Liu, Cun Ren; Elgavish, Ada; Morel, Laurence; Burrows, Peter D.; Schroeder, Harry W.
Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease that reflects a failure to block the production of self-reactive antibodies, especially those that bind double-stranded DNA (dsDNA). Backcrossing the lupus-prone NZM2410 genome onto C57BL/6 led to the identification of three genomic intervals, termed sle1, sle2 and sle3, which are associated with lupus susceptibility. We previously generated a C57BL/6 strain congenic for an immunoglobulin DH locus ( ΔD–iD ) that enriches for arginine at dsDNA-binding positions. We individually introduced the ΔD–iD allele into the three sle strains to test whether one or more of these susceptibility loci could affect the developmental fate of B cells bearing arginine-enriched CDR-H3s, the CDR-H3 repertoire created by the DH and the prevalence of dsDNA-binding antibodies. We found that the combination of the ΔD–iD allele and the sle1 locus led to a decrease in mature, recirculating B cell numbers and an increase in marginal zone cell numbers while maintaining a highly charged CDR-H3 repertoire. ΔD–iD and sle2 had no effect on peripheral B cell numbers, but the CDR-H3 repertoire was partially normalized. ΔD–iD and sle3 led to an increase in marginal zone B cell numbers, with some normalization of hydrophobicity. Mice with ΔD–iD combined with either sle1 or sle3 had increased production of dsDNA-binding IgM and IgG by 12 months of age. These findings indicate that the peripheral CDR-H3 repertoire can be categorically manipulated by the effects of nonimmunoglobulin genes.